A positive electrode lithium supplement additive and preparation method thereof, a positive electrode material for a lithium ion battery, a lithium ion battery and an electrical device
By doping transition metal into the lithium-ion battery positive electrode material Li5FeO4 and covering the large-radius element oxide layer and carbon layer, the problems of Li5FeO4 poor conductivity and poor environmental stability during use are solved, and higher structural stability and electrical conductivity are achieved.
Patent Information
- Application Number
- CN202411420638.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-12
AI Technical Summary
During use, the existing lithium-ion battery positive electrode material Li5FeO4 has problems such as poor electronic conductivity, poor environmental stability, excessive residual lithium and metal dissolution, which limits its commercial application prospects.
Lithium-rich lithium ferrate is used as the positive electrode lithium supplement additive, and the transition metal is doped by the core and the large-radius element oxide layer and carbon layer are successively coated to form a stable structure to improve the structural stability and environmental stability of the material.
It effectively alleviates the irreversible phase change of the material during charging and discharging, reduces the precipitation of oxygen, improves structural stability, reduces the risk of Fe dissolution, and improves conductivity and environmental stability.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a positive electrode lithium supplement additive and a preparation method thereof, a lithium ion battery positive electrode material, a lithium ion battery and an electrical device. Background Art
[0002] With the rapid development of portable electronic devices, electric vehicles and other application fields, high energy density lithium-ion batteries are urgently needed. Graphite, as a traditional negative electrode material, is used in commercial lithium-ion batteries. However, the theoretical specific capacity of graphite is low (372 mAh g −1 ), cannot meet the growing demand for high energy density. Silicon with extremely high theoretical capacity (4200mAh g −1 ) will be the ideal negative electrode for the next generation of high energy density batteries, but during the charge and discharge process, its huge volume change (>300%) and low initial efficiency (~70%) will significantly reduce the efficiency and capacity of the battery. When lithium-ion batteries are charged and discharged for the first time, a SEI film (solid electrolyte interface film) will form on the surface of the negative electrode material, consuming the active lithium in the positive electrode active material, resulting in a large irreversible capacity loss in the first week. In order to compensate for the capacity loss, it is necessary to use a lithium replenishment method to replenish the battery. The lithium replenishment method is divided into positive electrode lithium replenishment, negative electrode lithium replenishment and electrolyte lithium replenishment. Among them, positive electrode lithium replenishment has the advantages of high safety and low cost, and has become the mainstream method of lithium replenishment.
[0003] Li5FeO4 has a high theoretical specific capacity (867 mAh g −1 ) stands out among a number of lithium supplements. However, Li5FeO4 still has problems such as poor electronic conductivity, poor environmental stability, excessive residual lithium and metal dissolution during use, which greatly limits its commercial application prospects. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a positive electrode lithium supplement additive and a preparation method thereof, a lithium ion battery positive electrode material, a lithium ion battery and an electrical device.
[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0006] A positive electrode lithium supplement additive, the positive electrode lithium supplement additive is lithium iron-rich lithium, including a core and a large-radius element oxide layer and a carbon layer sequentially coated on the outer surface of the core, the chemical formula of the core is Li5Fe 1-x-y M x N yO4, where M is any one of Mg and Al, N is selected from any one of Ni, Mn, and Ti, 0.008 < x < 0.06, 0.002 ≤ y < 0.007, and the large-radius element oxide layer is any one of WO3 layer, Ta2O5 layer, and Nb2O5 layer. Compared with other common oxides, these oxides have larger ionic radii and are not easily doped into the matrix during sintering, thus damaging the matrix structure and causing a decrease in capacity.
[0007] For the above-mentioned cathode lithium supplement additive, preferably, the mass of the carbon layer is 1% - 4% of the mass of the core.
[0008] For the above-mentioned cathode lithium supplement additive, preferably, the mass of the transition metal in the large-radius element oxide layer is 0.3% - 1% of the mass of the core.
[0009] For the above-mentioned cathode lithium supplement additive, preferably, when the working voltage is 2.0 - 4.5V, its lithium supplement capacity is not less than 660 mAh / g.
[0010] As a general inventive concept, the present invention also provides a preparation method for the above-mentioned cathode lithium supplement additive, including the following steps:
[0011] (1) Mix a lithium source and an iron source according to a molar ratio of Li:Fe = 1.03 - 1.06:1, and then calcine to obtain LiFeO2;
[0012] (2) Mix the LiFeO2, lithium source, M source, and N source, and then sinter to obtain the core of the cathode lithium supplement additive;
[0013] (3) Mix the core of the cathode lithium supplement additive with a large-radius element oxide, and then sinter to obtain a material with a large-radius element oxide-coated core;
[0014] (4) Mix the material with a large-radius element oxide-coated core and a carbon material evenly, and then sinter to obtain the cathode lithium supplement additive.
[0015] For the above-mentioned preparation method, preferably, in step (1), the sintering is carried out in an air atmosphere, the sintering temperature is 500 - 700°C, and the sintering time is 8 - 12h.
[0016] For the above-mentioned preparation method, preferably, in step (2), the sintering is carried out in an inert gas, the sintering temperature is 700 - 850°C, and the sintering time is 8 - 15h.
[0017] In the above preparation method, preferably, in step (3), the sintering is carried out in an inert gas, the sintering temperature is 600-800° C., and the sintering time is 2-5 h.
[0018] In the above preparation method, preferably, in step (4), the sintering is carried out in an inert gas, the sintering temperature is 600-750° C., and the sintering time is 2-5 hours.
[0019] In the above preparation method, preferably, the inert gas is selected from N2, Ar or Ne; the inert gas introduction rate is 3-10 m 3 / h.
[0020] In the above preparation method, preferably, the lithium source includes at least one of lithium hydroxide, lithium carbonate and lithium oxide;
[0021] The iron source includes at least one of ferric oxide, ferric hydroxide and ferric chloride;
[0022] The M source is selected from at least one of a hydroxide, a chloride and an oxide containing element M;
[0023] The N source is selected from at least one of hydroxides, chlorides and oxides containing the N element;
[0024] The carbon material is selected from organic carbon materials, and the organic carbon material includes any one of phenolic resin, asphalt, sucrose and glucose.
[0025] As a general inventive concept, the present invention also provides a lithium-ion battery positive electrode material, including the positive electrode lithium replenishing additive mentioned above or including the positive electrode lithium replenishing additive prepared by the above preparation method.
[0026] For the above-mentioned positive electrode material for lithium-ion batteries, preferably, the mass of the positive electrode lithium supplement additive is 0.5%-3% of the mass of the positive electrode material for lithium-ion batteries.
[0027] As a general inventive concept, the present invention also provides a lithium-ion battery, comprising the above-mentioned lithium-ion battery positive electrode material.
[0028] As a general inventive concept, the present invention also provides an electrical device including the above-mentioned lithium-ion battery.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) In the positive electrode lithium supplement of the present invention, the core is doped with transition metals, and the shell is sequentially covered with a large-radius element oxide layer and a carbon layer. The element M is doped into the crystal lattice to occupy the Fe position, forming a strong MO bond to stabilize the crystal structure. The N element has a smaller ion radius and a high-valent compound of the N element is selected. Under high temperature conditions, after entering the crystal lattice, the valence balance can inhibit the precipitation of oxygen. Therefore, the synergistic effect of the dual doping of M and N elements can effectively alleviate the irreversible phase change of the material during the charging and discharging process, inhibit the precipitation of oxygen, have better structural stability, and reduce the risk of Fe dissolution caused by structural collapse after the first charge.
[0031] (2) In the positive electrode lithium supplement of the present invention, the core is doped with transition metal, and the shell is sequentially coated with a large-radius element oxide layer and a carbon layer. The large-radius element oxide layer is not easy to be doped into the matrix during the sintering process due to its larger ion radius, and will not destroy the matrix structure and cause a decrease in the overall capacity. The oxide can also react with the residual lithium on the surface of the core, thereby reducing the residual lithium of the lithium supplement, reducing the side reactions of the material during the application process, and effectively alleviating the erosion of the electrolyte on the core; the outermost layer is carbon-coated, which can not only improve the conductivity of the lithium supplement, but also because the carbon layer has a certain hydrophobicity, it can effectively reduce the reaction of the lithium supplement with water and carbon dioxide in the external environment, thereby improving the environmental stability of the material.
[0032] (3) In the preparation method of the present invention, a semi-finished product LiFeO2 is first synthesized, and then the semi-finished product is mixed with a doping element and a lithium source and sintered to obtain a core Li5Fe 1-x-y M x N y O4, compared with directly mixing the iron source, lithium source and doping elements, is more conducive to doping metal cations into the structure or grain boundaries, so that the bond energy of the formed MO and NO is greater than the bond energy of Fe-O, which can effectively alleviate the irreversible phase change of the material during the charging and discharging process, has better structural stability, and can effectively reduce the risk of Fe dissolution caused by structural collapse after the first charge of the material.
[0033] (4) The present invention obtains a positive electrode lithium supplement additive with stable structure and high capacity through double doping and double-layer coating modification. Applying it in lithium-ion batteries can effectively improve the capacity and cycle life of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a SEM image of the positive electrode lithium supplement additive prepared in Example 1 of the present invention;
[0035] Figure 2 This is a SEM image of the positive electrode lithium supplement additive prepared in Comparative Example 1 of the present invention;
[0036] Figure 3This is a comparison chart of the first charge and discharge curves of button cells prepared with the positive electrode lithium supplement additives of Example 1 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0038] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0040] Embodiment 1:
[0041] A positive electrode lithium supplement additive, comprising a core and a WO3 layer and a carbon layer sequentially coated on the outer surface of the core, wherein the chemical formula of the core is Li5Fe 0.955 Al 0.04 Mn 0.005 O4, the mass of the carbon layer is 3% of the mass of the core; the mass of W in the WO3 layer is 0.5% of the mass of the core.
[0042] The preparation method of the positive electrode lithium supplement additive of this embodiment comprises the following steps:
[0043] (1) Lithium carbonate and ferric oxide were mixed in a high-speed mixer at a molar ratio of Li:Fe = 1.03:1 at a speed of 1000 rpm for 30 min, and then the resulting mixture was heated to 700°C at a heating rate of 3°C / min and calcined for 10 h. The calcination was carried out in an air atmosphere at a rate of 5 m / min. 3 / h, after calcination, the material is crushed and sieved to obtain a calcined compound LiFeO2;
[0044] (2) The monosintered compound LiFeO2 prepared in step (1) was mixed with lithium oxide, aluminum oxide and manganese dioxide in a molar ratio of LiFeO2:Li2O:Al:Mn=0.955:2.023:0.04:0.005 in a high-speed mixer at a speed of 1000 rpm for 30 min, and then the prepared mixture was heated to 750°C at a heating rate of 3°C / min and calcined for 12 h, wherein the calcination was carried out in a nitrogen atmosphere at a nitrogen introduction rate of 5 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain the lithium supplement additive core Li5Fe 0.955 Al 0.04 Mn 0.005 O4;
[0045] (3) Li5Fe prepared in step (2) 0.955 Al 0.04 Mn 0.005 O4 and WO3 (calculated based on the core mass of 100%, W accounts for 0.5wt% of the core) were mixed in a high-speed mixer at a speed of 1000 rpm for 30 min, and then the prepared mixture was heated to 700 °C at a heating rate of 3 °C / min and calcined for 2 h. The calcination was carried out in a nitrogen atmosphere with a nitrogen introduction rate of 5 m / min. 3 / h, after calcination, the material is crushed and sieved to obtain the WO3-coated core material;
[0046] (4) The WO3-coated core material prepared in step (3) and asphalt (calculated based on the carbonization of asphalt accounting for 3 wt% of the core mass) were mixed in a high-speed mixer at a speed of 1000 rpm for 20 min, and then the prepared mixture was heated to 650°C at a heating rate of 3°C / min and calcined for 3 h, wherein the calcination was carried out in a nitrogen atmosphere at a nitrogen introduction rate of 10 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain the positive electrode lithium supplement additive, and its SEM image is as follows Figure 1 shown.
[0047] Embodiment 2:
[0048] A positive electrode lithium supplement additive, comprising a core and a WO3 layer and a carbon layer sequentially coated on the outer surface of the core, wherein the chemical formula of the core is Li5Fe 0.955 Al 0.04 Mn 0.005 O4, the mass of the carbon layer is 3% of the mass of the core; the mass of W in the WO3 layer is 1.2% of the mass of the core.
[0049] The preparation method of the positive electrode lithium supplement additive of this embodiment comprises the following steps:
[0050] (1) Lithium carbonate and ferric oxide were mixed in a high-speed mixer at a molar ratio of Li:Fe = 1.05:1 at a speed of 1000 rpm for 30 min, and then the resulting mixture was heated to 700°C at a heating rate of 3°C / min and calcined for 10 h. The calcination was carried out in an air atmosphere at an air introduction rate of 5 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain a calcined compound LiFeO2;
[0051] (2) The monosintered compound LiFeO2 prepared in step (1) was mixed with lithium oxide, aluminum oxide and manganese dioxide in a molar ratio of LiFeO2:Li2O:Al:Mn=0.955:2.023:0.04:0.005 in a high-speed mixer at a speed of 1000 rpm for 30 min, and then the prepared mixture was heated to 750°C at a heating rate of 3°C / min and calcined for 12 h, wherein the calcination was carried out in a nitrogen atmosphere at a nitrogen introduction rate of 5 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain the lithium supplement additive core Li5Fe 0.955 Al 0.04 Mn 0.005 O4;
[0052] (3) Li5Fe prepared in step (2) 0.955 Al 0.04 Mn 0.005 O4 and WO3 (calculated based on the core mass of 100%, W accounts for 1.2wt% of the core) were mixed in a high-speed mixer at a speed of 1000 rpm for 30 min, and then the prepared mixture was heated to 700°C at a heating rate of 3°C / min and calcined for 2 h. The calcination was carried out in a nitrogen atmosphere with a nitrogen introduction rate of 5 m / min. 3 / h, after calcination, the material is crushed and sieved to obtain the WO3-coated core material;
[0053] (4) The WO3-coated core material prepared in step (3) and asphalt (calculated based on the carbonization of asphalt accounting for 3 wt% of the core mass) were mixed in a high-speed mixer at a speed of 1000 rpm for 20 min, and then the prepared mixture was heated to 650°C at a heating rate of 3°C / min and calcined for 3 h, wherein the calcination was carried out in a nitrogen atmosphere at a nitrogen introduction rate of 10 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain the positive electrode lithium supplement additive.
[0054] Embodiment 3:
[0055] A positive electrode lithium supplement additive, comprising a core and a WO3 layer and a carbon layer sequentially coated on the outer surface of the core, wherein the chemical formula of the core is Li5Fe 0.946 Al 0.05 Mn 0.004 O4, the mass of the carbon layer is 5% of the mass of the core; the mass of W in the WO3 layer is 0.8% of the mass of the core.
[0056] The preparation method of the positive electrode lithium supplement additive of this embodiment comprises the following steps:
[0057] (1) Lithium carbonate and ferric oxide were mixed in a high-speed mixer at a molar ratio of Li:Fe = 1.06:1 at a speed of 1000 rpm for 30 min, and then the resulting mixture was heated to 650°C at a heating rate of 3°C / min and calcined for 10 h. The calcination was carried out in an air atmosphere at an air introduction rate of 5 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain a calcined compound LiFeO2;
[0058] (2) The monosintered compound LiFeO2 prepared in step (1) was mixed with lithium oxide, aluminum oxide and manganese dioxide in a high-speed mixer at a molar ratio of LiFeO2:Li2O:Al:Mn=0.946:2.027:0.05:0.004 at a speed of 1000 rpm for 30 min, and then the prepared mixture was heated to 800°C at a heating rate of 3°C / min and calcined for 15 h, wherein the calcination was carried out in a nitrogen atmosphere at a nitrogen introduction rate of 5 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain the lithium supplement additive core Li5Fe 0.946 Al 0.05 Mn 0.004 O4;
[0059] (3) Li5Fe prepared in step (2) 0.946 Al 0.05 Mn 0.004 O4 and WO3 (calculated based on the core mass of 100%, W accounts for 0.8wt% of the core) were mixed in a high-speed mixer at a speed of 1000 rpm for 30 min, and then the prepared mixture was heated to 650°C at a heating rate of 3°C / min and calcined for 2 h. The calcination was carried out in a nitrogen atmosphere with a nitrogen introduction rate of 5 m / min. 3 / h, after calcination, the material is crushed and sieved to obtain the WO3-coated core material;
[0060] (4) The WO3-coated core material prepared in step (3) and asphalt (calculated based on the carbonization of asphalt accounting for 5 wt% of the core mass) were mixed in a high-speed mixer at a speed of 1000 rpm for 20 min, and then the prepared mixture was heated to 700 °C at a heating rate of 3 °C / min and calcined for 5 h, wherein the calcination was carried out in a nitrogen atmosphere at a nitrogen introduction rate of 10 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain the positive electrode lithium supplement additive.
[0061] Embodiment 4:
[0062] A positive electrode lithium supplement additive, comprising a core and a Ta2O5 layer and a carbon layer sequentially coated on the outer surface of the core, wherein the chemical formula of the core is Li5Fe 0.958 Al 0.04 Ni 0.002 O4, the mass of the carbon layer is 2% of the mass of the core; the mass of Ta in the Ta2O5 layer is 0.4% of the mass of the core.
[0063] The preparation method of the positive electrode lithium supplement additive of this embodiment comprises the following steps:
[0064] (1) Lithium hydroxide and ferric oxide were mixed in a high-speed mixer at a molar ratio of Li:Fe = 1.03:1 at a speed of 1000 rpm for 30 min, and then the resulting mixture was heated to 700°C at a heating rate of 3°C / min and calcined for 10 h. The calcination was carried out in an air atmosphere at an air introduction rate of 5 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain a calcined compound LiFeO2;
[0065] (2) The monosintered compound LiFeO2 prepared in step (1) was mixed with lithium oxide, aluminum oxide and nickel dioxide in a molar ratio of LiFeO2:Li2O:Al:Ni=0.958:2.021:0.04:0.002 in a high-speed mixer at a speed of 1000 rpm for 30 min, and then the prepared mixture was heated to 750°C at a heating rate of 3°C / min and calcined for 15 h, wherein the calcination was carried out in a nitrogen atmosphere at a nitrogen introduction rate of 5 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain the lithium supplement additive core Li5Fe 0.958 Al 0.04 Ni 0.002 O4;
[0066] (3) Li5Fe prepared in step (2) 0.958 Al 0.04 Ni 0.002 O4 and Ta2O5 (Ta accounts for 0.4wt% of the core, calculated as 100% by mass of the core) were mixed in a high-speed mixer at a speed of 1000 rpm for 30 min, and then the prepared mixture was heated to 600°C at a heating rate of 3°C / min and calcined for 2 h. The calcination was carried out in a nitrogen atmosphere with a nitrogen introduction rate of 5 m / min. 3 / h, after calcination, the material is crushed and sieved to obtain Ta2O5-coated core material;
[0067] (4) The Ta2O5-coated core material prepared in step (3) and asphalt (calculated based on the carbonization of asphalt accounting for 2 wt% of the core mass) were mixed in a high-speed mixer at a speed of 1000 rpm for 20 min, and then the prepared mixture was heated to 650°C at a heating rate of 3°C / min and calcined for 3 h, wherein the calcination was carried out in a nitrogen atmosphere at a nitrogen introduction rate of 10 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain the positive electrode lithium supplement additive.
[0068] Embodiment 5:
[0069] A positive electrode lithium supplement additive, comprising a core and a WO3 layer and a carbon layer sequentially coated on the outer surface of the core, wherein the chemical formula of the core is Li5Fe 0.985 Mg 0.01 Mn 0.005 O4, the mass of the carbon layer is 2% of the mass of the core; the mass of W in the WO3 layer is 0.5% of the mass of the core.
[0070] The preparation method of the positive electrode lithium supplement additive of this embodiment comprises the following steps:
[0071] (1) Lithium hydroxide and ferric oxide were mixed in a high-speed mixer at a molar ratio of Li:Fe = 1.03:1 at a speed of 1000 rpm for 30 min, and then the resulting mixture was heated to 700°C at a heating rate of 3°C / min and calcined for 10 h. The calcination was carried out in an air atmosphere at an air introduction rate of 5 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain a calcined compound LiFeO2;
[0072] (2) The monosintered compound LiFeO2 prepared in step (1) was mixed with lithium oxide, magnesium oxide and manganese dioxide in a molar ratio of LiFeO2:Li2O:Mg:Mn=0.985:2.008:0.01:0.005 in a high-speed mixer at a speed of 1000 rpm for 30 min, and then the prepared mixture was heated to 750°C at a heating rate of 3°C / min and calcined for 12 h, wherein the calcination was carried out in a nitrogen atmosphere at a nitrogen introduction rate of 5 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain the lithium supplement additive core Li5Fe 0.985 Mg 0.01 Mn 0.005 O4;
[0073] (3) Li5Fe prepared in step (2) 0.985 Mg 0.01 Mn 0.005O4 and WO3 (calculated based on the core mass of 100%, W accounts for 0.5wt% of the core) were mixed in a high-speed mixer at a speed of 1000 rpm for 30 min, and then the prepared mixture was heated to 700 °C at a heating rate of 3 °C / min and calcined for 2 h. The calcination was carried out in a nitrogen atmosphere with a nitrogen introduction rate of 5 m / min. 3 / h, after calcination, the material is crushed and sieved to obtain the WO3-coated core material;
[0074] (4) The WO3-coated core material prepared in step (3) and asphalt (calculated based on the carbonization of asphalt accounting for 2 wt% of the core mass) were mixed in a high-speed mixer at a speed of 1000 rpm for 20 min, and then the prepared mixture was heated to 650°C at a heating rate of 3°C / min and calcined for 3 h, wherein the calcination was carried out in a nitrogen atmosphere at a nitrogen introduction rate of 10 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain the positive electrode lithium supplement additive.
[0075] Comparative Example 1:
[0076] The lithium supplement additive in this comparative example is Li5FeO4, and its preparation method is as follows: lithium oxide and ferric oxide are mixed in a high-speed mixer at a molar ratio of Li:Fe = 5:1 at a speed of 1000 rpm for 30 minutes, and then the resulting mixture is heated to 800°C at a heating rate of 3°C / min and calcined for 12 hours, wherein the calcination is carried out in a nitrogen atmosphere, and the nitrogen introduction rate is 5m / min. 3 / h, after calcination, the material is crushed and sieved to obtain the lithium supplement additive Li5FeO4, whose SEM picture is as follows Figure 2 shown.
[0077] Comparative Example 2:
[0078] The lithium supplement additive in this comparative example is Li5Fe 0.955 Al 0.04 Mn 0.005 O4, the preparation method is as follows: lithium hydroxide, iron oxide, aluminum oxide, and manganese oxide are mixed in a high-speed mixer at a molar ratio of Li:Fe:Al:Mn = 5.05:0.955:0.04:0.005 at a speed of 1000 rpm for 30 min, and then the resulting mixture is heated to 750°C at a heating rate of 3°C / min and calcined for 12 h, wherein the calcination is carried out in a nitrogen atmosphere at a nitrogen introduction rate of 5 m / min. 3 / h, after calcination, the material is crushed and sieved to obtain the lithium supplement additive Li5Fe 0.955 Al 0.04 Mn 0.005 O4.
[0079] Comparative Example 3:
[0080] The lithium supplement additive in this comparative example is WO3 and carbon co-coated Li5Fe 0.955 Al 0.04 Mn 0.005 O4, the preparation method thereof is as follows:
[0081] (1) Lithium carbonate and ferric oxide were mixed in a high-speed mixer at a molar ratio of Li:Fe = 1.03:1 at a speed of 1000 rpm for 30 min, and then the resulting mixture was heated to 700°C at a heating rate of 3°C / min and calcined for 10 h. The calcination was carried out in an air atmosphere at a rate of 5 m / min. 3 / h, after calcination, the material is crushed and sieved to obtain a calcined compound LiFeO2;
[0082] (2) The monosintered compound LiFeO2 prepared in step (1) was mixed with lithium oxide, aluminum oxide and manganese dioxide in a molar ratio of LiFeO2:Li2O:Al:Mn=0.955:2.023:0.04:0.005 in a high-speed mixer at a speed of 1000 rpm for 30 min, and then the prepared mixture was heated to 750°C at a heating rate of 3°C / min and calcined for 12 h, wherein the calcination was carried out in a nitrogen atmosphere at a nitrogen introduction rate of 5 m / s. 3 / h, after calcination, the material is crushed and sieved to obtain the lithium supplement additive core Li5Fe 0.955 Al 0.04 Mn 0.005 O4;
[0083] (3) Li5Fe prepared in step (2) 0.955 Al 0.04 Mn 0.005 O4, WO3 (calculated based on the core mass of 100%, W accounting for 0.5wt% of the core) and asphalt (calculated based on the carbonization of asphalt accounting for 3wt% of the matrix mass) were mixed in a high-speed mixer at a speed of 1000rpm for 30min, and then the prepared mixture was heated to 650℃ at a heating rate of 3℃ / min and calcined for 3h, wherein the calcination was carried out in a nitrogen atmosphere with a nitrogen introduction rate of 8m / min. 3 / h, after calcination, the material is crushed and sieved to obtain a lithium supplement additive.
[0084] Comparative Example 4:
[0085] The lithium supplement additive in this comparative example includes a core Li5Fe 0.955 Al 0.04 Mn 0.005O4 and the carbon layer and WO3 layer sequentially coated on the outer surface of the inner core.
[0086] The difference between the preparation method of the positive electrode lithium supplement additive prepared in this comparative example and that in Example 1 is that the preparation order of step (3) and step (4) is exchanged, that is, carbon coating is first performed on the core, and then WO3 coating is performed, and the other process parameters are completely the same.
[0087] The above embodiments and comparative examples are assembled into button cells. The specific assembly method is: mix the lithium supplement agent: SP: PVDF in a mass ratio of 80:10:10 to make a slurry, apply and dry to prepare the positive electrode, the negative electrode is a lithium sheet, the electrolyte is 1.2mol / LLiPF6 / EC-DMC (1:1), and the polypropylene microporous film is a diaphragm. The positive electrode, negative electrode, and diaphragm are normally assembled into a button cell in a glove box protected by a nitrogen atmosphere. When testing the electrochemical performance, the working voltage of the button cell is 2.0-4.5V, and the current density is 40mA / g.
[0088] The lithium supplement additives of the above embodiments and comparative examples were tested for residual LiOH on the surface by acid-base titration, and the test solvent was anhydrous ethanol; the powder resistivity was tested by Yuanneng powder resistivity and compaction density tester equipment (the corresponding resistivity data under a pressure of 160MPa was taken); the iron dissolution results were all obtained by charging the assembled button battery to 4.5V for the first time at a high temperature of 45°C at a rate of 0.05C (1C=800mA / g), and then removing the battery for disassembly after constant voltage for 12h, taking out the negative electrode sheet, and then digesting it, using ICP to test the iron content in the solution, and then calculating the unit dissolution value of Fe in the lithium-rich lithium ferrite lithium supplement, wherein the unit dissolution value of Fe = (test value-blank value)*dilution multiple / (mass of active material of the electrode sheet*1000).
[0089] The results are shown in Table 1. The comparison of the first charge and discharge curves of the button cells prepared in Example 1 and Comparative Examples 1-3 is shown in Figure 3 shown.
[0090] Table 1 Performance data of lithium supplement additives of various embodiments and comparative examples
[0091]
[0092] It can be seen from Table 1 that in the positive electrode lithium replenishing additive of the present invention, the core is doped with transition metal, and the shell is sequentially coated with a large-radius element oxide layer and a carbon layer, which can effectively enhance the structural stability of the material and reduce the risk of Fe dissolution caused by structural collapse after the first charge; at the same time, the coating layer of the shell can not only effectively alleviate the erosion of the electrolyte on the core, but also effectively reduce the contact between the core and the external environment, thereby improving the environmental stability of the material. The large-radius element oxide in the middle layer can significantly reduce the residual lithium on the surface, and the outermost carbon layer can significantly improve the electrical conductivity of the material. Doping Li5FeO4 and adding double-layer coating modification can obtain a positive electrode lithium replenishing additive with stable structure and high capacity.
[0093] By comparing the data of Example 1 with Comparative Examples 1-2, it can be seen that doping with transition metals can effectively enhance the stability of the material structure and alleviate the Fe dissolution phenomenon after the first charge. Compared with undoped Li5FeO4, its first charge capacity and lithium replenishment capacity are higher. Combining doping and coating at the same time can significantly improve the electronic conductivity of the material, stabilize the surface structure, reduce the contact between the core and the external environment, and improve the environmental stability of the material. Figure 1 and Figure 2 It can be seen from the electron microscope image that the uncoated Li5FeO4 in Comparative Example 1 has a rough surface, while the coated lithium supplement of Example 1 has a smoother surface and less side reactions between the material and the electrolyte.
[0094] By comparing the test data of Example 1 with Comparative Examples 3-4, it can be seen that compared with coating oxide and carbon material at the same time, coating oxide first and then coating carbon material, oxide coating can first reduce the residual lithium on the surface, and in the subsequent carbon coating process, the oxide layer can isolate part of the water and carbon dioxide in the air, reduce the possibility of adverse reactions in the kernel, and thus form a good double-layer structure. However, when oxide and carbon material are mixed and coated at the same time, uneven coating may occur, and a good double-layer coating structure cannot be formed. There is also a risk of the kernel reacting with the external environment during the mixing process. The residual lithium hydroxide on the surface in Comparative Example 3 is 2.2%, which is greater than 0.55% of Example 1, and its capacity is 16.2 mAh / g lower than that of Example 1, which also confirms the above conclusion. In Comparative Example 4, which first coats carbon and then coats the oxide layer, since the oxide is an inert substance, the oxide layer in the outermost layer will cause the conductivity of the lithium supplement to decrease, and affect the transmission of lithium ions in the subsequent charge and discharge process, thereby causing the capacity of the lithium supplement to decrease.
[0095] By comparing the data of Example 1 and Example 2, it can also be seen that when the carbon coating content is consistent and the oxide coating amount is greater than 1wt% (the mass fraction of the inner core), some adverse results will occur. If the coating amount is too large, the oxide and the inner core may react to cause partial incorporation of elements, affecting the main structure of the inner core, thereby causing a decrease in capacity.
[0096] By comparing the data of Example 1 and Example 3, it can be seen that when the carbon coating is greater than 4%, the conductivity of the material increases, but the increase in the thickness of the coating layer will hinder the Li + transmission, resulting in a reduction in material capacity.
[0097] The Li5FeO4 of comparative example 1 was mixed with the positive electrode material LiCoO2 in a weight ratio of 2:100, and the positive electrode lithium supplement additive prepared in Example 1 was mixed with the positive electrode material LiCoO2 in a weight ratio of 1:100, 2:100, 3:100, and 3.5:100, respectively. When the positive electrode material was prepared, the active material: conductive carbon black (SP): polyvinylidene fluoride (PVDF) was mixed in a weight ratio of 94:3:3; when the negative electrode material was prepared, the negative electrode active material was SiO / C (mass ratio was 1:9), and the negative electrode active material: conductive agent acetylene black: thickener CMC: binder SBR = 96:1:1:2 were mixed; the electrolyte was 1.2 mol / LLiPF6 / EC–DMC (1:1), and the polypropylene microporous film was used as the diaphragm. The specific process of battery production includes: batching, homogenization, coating, rolling, tab welding, winding, top sealing, liquid injection, formation, punching, and assembly of positive and negative electrodes into soft-pack batteries. The soft-pack batteries assembled above were subjected to electrochemical charge and discharge tests using a blue battery test system with a voltage range of 3.0 to 4.5 V and 0.1C / 0.1C for the first charge and discharge. The first charge and discharge efficiency and the capacity retention rate after 100 cycles (1C / 1C) were recorded. The results are shown in Table 2.
[0098] Table 2 Electrochemical properties of soft-pack batteries prepared with lithium supplement additives in Comparative Example 1 and Example 1
[0099]
[0100] It can be seen from the data in Table 2 that the capacity and cycle life of the whole battery can be improved by mixing the lithium supplement additive with the positive electrode material in proportion; when the addition amount of comparative example 1 and example 1 accounts for 2wt% of the positive electrode material LiCoO2, the addition of the lithium supplement additive prepared in example 1 has a greater improvement in the full capacity and 100-week cycle retention rate, which also shows that the lithium supplement additive of the present invention can make the capacity of the material more stable, and the product after decomposition after lithium removal is more stable, and has less impact on the positive electrode material. When the addition amount of the lithium supplement additive is 3.5wt%, its discharge capacity and cycle performance are lower than those of the addition amount of 3wt%, which shows that the addition of lithium supplement additives is not the more the better. When the addition amount exceeds the optimal design amount, it will have a negative effect. The active substance is composed of the positive electrode material and the lithium supplement agent. When the addition amount of the lithium supplement agent is too large, the intrinsic capacity will be reduced due to the small proportion of the positive electrode material, and the products of the excessive lithium supplement agent after the first charge will hinder Li + transport, and as the material begins to cycle, the polarization increases, resulting in a decrease in cycle performance.
[0101] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A positive electrode lithium supplement additive, characterized in that: The positive electrode lithium supplement additive includes a core and a large-radius element oxide layer and a carbon layer that are sequentially coated on the outer surface of the core. The chemical formula of the core is Li5Fe 1-x-y M x N y O4, where M is any one of Mg and Al, N is selected from any one of Ni, Mn, and Ti, 0.008 < x < 0.06, 0.002 ≤ y < 0.007, and the large-radius element oxide layer is any one of WO3 layer, Ta2O5 layer, and Nb2O5 layer; The mass of the carbon layer is 1%-4% of the mass of the core; The mass of the transition metal element in the large-radius element oxide layer is 0.3%-1% of the mass of the inner core.
2. The positive electrode lithium supplement additive according to claim 1, characterized in that: When the working voltage of the positive electrode lithium replenishing additive is 2.0-4.5V, the lithium replenishing capacity of the positive electrode lithium replenishing additive is not less than 660 mAh / g.
3. A method for preparing a positive electrode lithium supplement additive as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Mixing a lithium source and an iron source and calcining them to obtain LiFeO2; (2) mixing the LiFeO2, lithium source, M source and N source and sintering them to obtain a positive electrode lithium supplement additive core; (3) mixing the positive electrode lithium supplement additive core with the large radius element oxide and sintering them to obtain a large radius element oxide coated core material; (4) After the large-radius element oxide-coated core material and the carbon material are uniformly mixed, they are sintered to obtain the positive electrode lithium supplement additive.
4. The preparation method according to claim 3, characterized in that: In step (1), the sintering is carried out in an air atmosphere, the sintering temperature is 500-700° C., and the sintering time is 8-12 hours; In step (2), the sintering is carried out in an inert gas, the sintering temperature is 700-850° C., and the sintering time is 8-15 hours; In step (3), the sintering is carried out in an inert gas, the sintering temperature is 600-800° C., and the sintering time is 2-5 hours; In step (4), the sintering is carried out in an inert gas, the sintering temperature is 600-750° C., and the sintering time is 2-5 hours.
5. The preparation method according to claim 4, characterized in that The inert gas is selected from N2, Ar or Ne; the inert gas introduction rate is 3-10 m 3 / h.
6. The preparation method according to claim 3, characterized in that: The lithium source includes at least one of lithium hydroxide, lithium carbonate and lithium oxide; The iron source includes at least one of ferric oxide, ferric hydroxide and ferric chloride; The M source is selected from at least one of a hydroxide, a chloride and an oxide containing element M; The N source is selected from at least one of hydroxides, chlorides and oxides containing the N element; The carbon material is selected from organic carbon materials.
7. A positive electrode material for a lithium ion battery, characterized in that: The invention comprises the positive electrode lithium supplement additive according to any one of claims 1 to 2 or comprises the positive electrode lithium supplement additive prepared by the preparation method according to any one of claims 3 to 6.
8. The lithium ion battery positive electrode material according to claim 7, characterized in that The mass of the positive electrode lithium supplement additive is 0.5%-3% of the mass of the positive electrode material of the lithium ion battery.
9. A lithium ion battery, characterized in that: Comprising the lithium-ion battery positive electrode material as claimed in claim 7 or 8.
10. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 9.
Citation Information
Patent Citations
Lithium supplement additive and preparation method and application thereof
CN116072991A
Positive electrode lithium supplement additive and preparation method thereof, lithium-rich positive electrode and secondary battery
CN116544533A